ESTIMATION OF POTENTIAL WATER AVAILABILITY AND WATER RESOURCES CARRYING CAPACITY FOR BOGOR CITY SPATIAL PLAN - Juniati, Atie Tri; Kusratmoko, Eko; Sutjiningsih, Dwita (UI Scholars Hub, 2021)
The aim of the present research is to examine the effectiveness of rational method widely used in calculating water availability for spatial planning in Indonesia. The rational method is developed mainly for estimating the characteristics of drainage infrastructure instead of estimating water availability. The effectiveness of rational method and Soil-Conservation Service Curve Number (SCS-CN) method are compared by testing their performance in estimating water availability in the Upper Cisadane river basin in West Java, Indonesia. The results shows that calibrated SCS-CN model performs better than Rational model with R2 and NSE of 0,62 and 0,37. Result of model validation yields R2 = 0,73 and NSE = 0,52. The result suggests that SCS-CN performs better than the rational model in simulating the character of water catchment area and is suitable for model of choice in water availability estimation.